2019
DOI: 10.1002/smll.201802891
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Phenotyping and Modulation of ALDH+ Inflammatory Breast Cancer Stem‐Like Cells

Abstract: Cancer stem-like cells (CSCs) have been shown to initiate tumorigenesis and cancer metastasis in many cancer types. Although identification of CSCs through specific marker expression helps define the CSC compartment, it does not directly provide information on how or why this cancer cell subpopulation is more metastatic or tumorigenic. In this study, we comprehensively profiled the functional and biophysical characteristics of aggressive and lethal inflammatory breast cancer (IBC) CSCs at the single-cell level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…In addition, to validate the contribution of biophysical properties in metastasis, the authors isolated IBC cells based on their adhesive property using a microfluidic device and showed that the less adhesive cell population was ALDH+ enriched, displayed enhanced in vitro invasion and migration as well as increased in vivo tumor development. Further, exogenous alteration of cell stiffness also resulted in changes in metastatic potential of these cells with less stiff cells showing greater invasion and migration (Chen, Allen et al 2019). The results observed in this study corroborated well with earlier studies showing that cancer cells with greater deformability, lower adhesion strength and lower contractile force show enhanced metastatic potential (Swaminathan, Mythreye et al 2011, Kraning-Rush, Califano et al 2012, Byun, Son et al 2013, Sun, Luo et al 2016, Bongiorno, Gura et al 2018).…”
Section: Biophysical Characterization Of Cscs and Their Subsetssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, to validate the contribution of biophysical properties in metastasis, the authors isolated IBC cells based on their adhesive property using a microfluidic device and showed that the less adhesive cell population was ALDH+ enriched, displayed enhanced in vitro invasion and migration as well as increased in vivo tumor development. Further, exogenous alteration of cell stiffness also resulted in changes in metastatic potential of these cells with less stiff cells showing greater invasion and migration (Chen, Allen et al 2019). The results observed in this study corroborated well with earlier studies showing that cancer cells with greater deformability, lower adhesion strength and lower contractile force show enhanced metastatic potential (Swaminathan, Mythreye et al 2011, Kraning-Rush, Califano et al 2012, Byun, Son et al 2013, Sun, Luo et al 2016, Bongiorno, Gura et al 2018).…”
Section: Biophysical Characterization Of Cscs and Their Subsetssupporting
confidence: 90%
“…Similar to biochemical heterogeneity observed within CSCs (Bocci, Gearhart-Serna et al 2019, Moreira, Brayner et al 2019), CSCs can be biophysically strikingly different too In a recent study, Chen et al, showed the association of biophysical properties of CSCs and their ability to invade, migrate, and initiate tumors, using the SUM149 inflammatory breast cancer (IBC) stem cells (Chen, Allen et al 2019). In this study, the authors sorted SUM149 CSCs based on the expression of aldehyde dehydrogenase enzyme (ALDH) and assayed biophysical properties of ALDH+ and ALDH-cells in terms of deformability, adhesion strength and contractility.…”
Section: Biophysical Characterization Of Cscs and Their Subsetsmentioning
confidence: 96%
“…A previous investigation using AFM reported a 0.7-fold lower stiffness in a human hepatoma stem cell line, MHCC97H, compared with that of the parental cells 26 . Other researchers using a microfluidic device reported a higher deformability in ALDH + CSCs isolated from an inflammatory breast cancer cell line, SUM149, than that in ALDH − cells 27 . Cross et al first reported that the average Young's modulus value for metastatic cancer cells isolated from the pleural fluid of lung, breast, and pancreatic cancer patients tended to be approximately 0.33-fold lower than that of normal mesothelial cells 8 .…”
Section: Discussionmentioning
confidence: 90%
“…Similar to biochemical heterogeneity observed within CSCs (Bocci et al, 2019;Moreira et al, 2019), CSCs can be biophysically strikingly different too ( Table 2). In a recent study, Chen et al (2019) showed the association of biophysical properties of CSCs and their ability to invade, migrate, and initiate tumors, using the SUM149 inflammatory breast cancer (IBC) stem cells. In this study, the authors sorted SUM149 CSCs based on the expression of aldehyde dehydrogenase enzyme (ALDH) and assayed biophysical properties of ALDH+ and ALDH-cells in terms of deformability, adhesion strength and contractility.…”
Section: Biophysical Characterization Of Cscs and Their Subsetsmentioning
confidence: 99%